Convicting the Innocent: An Analysis of the Effects of Wrongful Convictions and Available Remedies in Canada - Pacholski, Casandra; Anderson, Gail S. (The Wrongful Conviction Law Review, 2023)
The past three decades have seen at least 3,200 exonerations across North America. While this number continues to grow, attention must be turned to facilitating successful re-entry amongst this group. By conducting a content analysis of 57 Canadian exonerees, I gathered demographics and common case characteristics to assess the re-entry success of exonerees. Successful re-entry was incredibly difficult for the majority of exonerees due to a lack of specialized re-entry services, counselling, compensation legislation, and healthcare. Exonerees are suffering in the same ways as legitimate offenders while incarcerated and afterward, all while being offered drastically less assistance from Canada’s institutions and government